Advances in chronohaematology - Berger, Josef (Journal of Applied Biomedicine, 2008)
The circadian rhythms of the haemato-immune system seem to be synchronized by two clocks: the hypothalamic endogenous, and the exogenous which is based on environmental stimuli. The suprachiasmatic nucleus is not only a circadian clock, it also synchronizes peripheral oscillators and integrates light information through the retino-hypothalamic tract. The role of the “peripheral” clock genes in mature leucocytes still remains an unanswered question as well as the role of clock proteins in “non-clock” physiology. The circadian rhythms may be a basis for circannual variations, although the molecular bases of such rhythms remain a mystery. There are several hormones which have a significant impact on haematological characteristics; the finding of a lower superoxide release from granulocytes at higher melatonin levels opens up new research opportunities for melatonin therapy. Discrepancies between circadian changes in mRNAs and the appropriate protein participating in haemocoagulation and fibrinolysis may indicate that we do not know their control processes or their genetic background well, although this problem has now opened up a new area for pharmacological research. The endogenous clock facilitates an alternation in the immune system which counters external attacks in daytime and induces repair and development by night.
Keywords: cirkadiánní rytmus; biologické hodiny; Melatonin; Financing, Organized; Circadian Rhythm; Immunity; Hemostasis; imunita; Superoxides; financování organizované; superoxidy; roční období; Seasons; melatonin; Biological Clocks; hemostáza